ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KOTA BATAM - SITORUS, PRETTY; Br. Purba, Neni Marlina (SCIENTIA JOURNAL, 2023)
This study aims to determine the factors that influence motor vehicle tax compliance in Batam City. This research consists the variables of Taxpayer Understanding (X1), Taxpayer Awareness (X2), Service Quality (X3), Tax Sanctions (X4) on Taxpayer Compliance (Y). This study uses quantitative data types, while the data source uses primary data with data collection techniques is by distributing questionnaires. The data processing technique used was data processing with SPSS software version 25. Based on the results of the study, it was concluded that partially the variables of Taxpayer Understanding (X1), Taxpayer Awareness (X2), Service Quality (X3) and Tax Sanctions (X4) show a significant effect on Taxpayer Compliance (Y). But together the variables of understanding of taxpayers (X1), awareness of taxpayers (X2), quality of service (X3), tax penalties (X4) show an effect on taxpayer compliance (Y). The coefficient of determination of 69.2% indicates that the variable Taxpayer Understanding (X1), Taxpayer Awareness (X2), Service Quality (X3), Tax Sanctions (X4) has an effect of 69.2% on Taxpayer Compliance (Y) and the remaining 30.8% is influenced by other variables that were not examined in this study.